APLIKASI PROXIMITY BEACON SEBAGAI SENSOR ANTI TABRAKAN MENGGUNAKAN MICROBIT UNTUK PEMBELAJARAN PEMROGRAMAN SISWA-SISWI SMP DI SEKOLAH HAMIDAH SAMPURNA, KABUPATEN BANDUNG - Novamizanti, Ledya; Iwut Tritoasmoro, Iwan; Fardan, Fardan; Danny Adviatmadja, Sebastian; Imansyah Basudewa , Muhammad; Aqilah Mamur Tanjung , Najmi (Jurnal Abdi Insani, 2025)
The development of digital technology requires the young generation to have technological literacy and programming skills from an early age. To answer this challenge, the community service team from the Electrical Engineering Faculty of Telkom University carried out activities at Hamidah Sampurna Junior High School (SHS), Bandung Regency. This activity has the theme "Proximity Beacon Application Using Microbit as Anti-Collision Car Sensor." The activity was carried out on May 28, 2025 and involved various educational elements. The purpose of this activity is to introduce technology and programming to junior high school students through a practical and project-based approach. The activity method is conducted through direct training using Microbit devices designed according to the level of understanding of junior high school students. This activity also involved teachers, parents, and students with a total of 47 participants. The results of the survey showed that 63.8% of participants strongly agreed that the material was appropriate, 76.6% rated the technology presented as very useful, and 89.4% stated that the material was easy to understand. A total of 91.5% of participants hope that similar activities can be continued in the future. This activity shows the high enthusiasm of the participants and the effectiveness of the project-based approach. Collaboration between schools, parents, and universities strengthens the learning process. This activity also improves students' digital literacy and programming skills. This activity successfully builds educational synergy and is recommended to be expanded with advanced technologies such as IoT and AI.